The spatial clustering patterns of the U.S hotels during 1985–2017. Issue 3 (3rd July 2018) - Kim, Young-Rae; Kim, Jin-Won; Huh, Chang
ABSTRACT: 'Location, location, location' are treated as three sacred words in the lodging industry because location plays a significant role in the industry's success. However, little attention has been paid to understanding hotel locations in regional contexts. The purpose of this study was to investigate spatial clustering patterns of hotels over time in relation to hotel locations and regions in the U.S. The Smith Travel Research (STR) Hotel Census Data from 1985 to 2017 were used for the study, and a series of statistical analyses was carried out to examine the relationships among the identified patterns. The results indicated that hotel locations and development were concentrated in specific geographical regions during the study periods. The implications of the study are discussed.